MODERNIZING THE ISLAMIC EDUCATION CURRICULUM: INTEGRATION OF TRADITIONAL VALUES WITH TECHNOLOGICAL INNOVATION TO IMPROVE 21ST CENTURY COMPETENCIES - Habibi, Rab’ul; Zamroni, Zamroni; Tamam, Badrut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Modernizing the Islamic education curriculum is an urgent need in the era of globalization and technological development. Traditional curricula, although effective in forming spiritual values, tend to be less relevant in meeting the demands of 21st century skills, such as critical thinking, digital literacy, and global collaboration. This research aims to analyze the current condition of the Islamic education curriculum, identify the main challenges in the modernization process, and examine strategies for integrating Islamic values with technology and contemporary pedagogical approaches. This research approach is qualitative with descriptive-analytical methods. Data was collected through literature studies, in-depth interviews, observations, and case studies at Islamic educational institutions in Indonesia. The research results show that cultural resistance, limited access to technology, and low readiness of teaching staff are the main challenges in curriculum modernization. However, great opportunities can be optimized through the application of learning technology, competency-based curricula and multidisciplinary approaches. This research concludes that modernizing the Islamic education curriculum is a strategic step to create a generation of Muslims who are spiritually, intellectually and professionally competent. With a synergy between traditional values and modern innovation, Islamic education can be a means of transformation towards an education system that is relevant, inclusive and adaptive to global needs.